The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Snake Venoms 2016
DOI: 10.1007/978-94-007-6648-8_31-1
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venom Components Affecting the Coagulation System

Abstract: Snake venoms are rich sources of proteases of medical importance that affect hemostasis. In this chapter, the factors affecting blood coagulation are classified into two separate groups: the procoagulant and the anticoagulant proteins. The procoagulant proteins are subclassified as clotting factor activators and thrombinlike enzymes. The anticoagulant proteins are able to prevent blood clotting and maintain blood incoagulability and can include phospholipases A2, fibrin(ogen) olytics, protein C activator, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…48 Furthermore, Zhang and Du 2021, 49 disclosed that the most lethal enzyme in BV formation of the melittin-PLA2 complex is referred to as the bee hemolytic factor which cleaves cellular membrane phospholipids and cellular lysis. Moreover, Alvarez-Flores et al, 2016, 50 indicated that the PLA2 had a hematological effect including coagulation abnormalities. Moreover, Abdulsalam et al, 2016, 46 reported that PLA2 from BV inhibited platelet aggregation through the formation of lysophosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…48 Furthermore, Zhang and Du 2021, 49 disclosed that the most lethal enzyme in BV formation of the melittin-PLA2 complex is referred to as the bee hemolytic factor which cleaves cellular membrane phospholipids and cellular lysis. Moreover, Alvarez-Flores et al, 2016, 50 indicated that the PLA2 had a hematological effect including coagulation abnormalities. Moreover, Abdulsalam et al, 2016, 46 reported that PLA2 from BV inhibited platelet aggregation through the formation of lysophosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…To interpret the result, it is important to consider that proteins as SVSP, SVMP, CTL, PLA 2 and other toxins play roles in the coagulation process. Some are procoagulant and others are anticoagulant [61]. Thus, synergistic effect [14,62] and a balance of actions produce the final venom activity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high specificity, RVV-X is a remarkable biotechnological tool widely used in coagulation research and medical diagnostics. ,, For example, the Stypven time is determined by a clotting assay that measures the FX to FXa conversion by RVV-X and subsequent prothrombin activation that initiates clot formation. In particular, a long Stypven time is a diagnostic of FX deficiency, also called Stuart–Prower factor deficiency …”
Section: Introductionmentioning
confidence: 99%